2019
DOI: 10.1038/s41467-019-10039-w
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal gel elasticity arises from the packing of locally glassy clusters

Abstract: Colloidal gels formed by arrested phase separation are found widely in agriculture, biotechnology, and advanced manufacturing; yet, the emergence of elasticity and the nature of the arrested state in these abundant materials remains unresolved. Here, the quantitative agreement between integrated experimental, computational, and graph theoretic approaches are used to understand the arrested state and the origins of the gel elastic response. The micro-structural source of elasticity is identified by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 48 publications
11
116
0
Order By: Relevance
“…where Z∞ is the average coordination number of a hard-sphere suspension at a given shear rate ( are not sufficient to break the particulate network globally, they provide the particles near the surface of locally-glassy clusters [45] with additional energy required to occasionally break their bonding interactions and explore a more stable global state with progressively larger number of bonds [12,18]. Recently, Whitaker et al [45] through graph theory and structural analysis of the particle configurations showed that in gels formed under quiescent conditions as well as under flowing conditions, the elasticity of the gel arises from the packing of locally glassy clusters.…”
Section:  mentioning
confidence: 99%
See 1 more Smart Citation
“…where Z∞ is the average coordination number of a hard-sphere suspension at a given shear rate ( are not sufficient to break the particulate network globally, they provide the particles near the surface of locally-glassy clusters [45] with additional energy required to occasionally break their bonding interactions and explore a more stable global state with progressively larger number of bonds [12,18]. Recently, Whitaker et al [45] through graph theory and structural analysis of the particle configurations showed that in gels formed under quiescent conditions as well as under flowing conditions, the elasticity of the gel arises from the packing of locally glassy clusters.…”
Section:  mentioning
confidence: 99%
“…shear viscosity, loss and storage moduli, as well as electrical conductivity. Furthermore, fast confocal microscopy of sheared attractive colloids have also shown the role of prior shear history and the rate of applied deformation in controlling the microstructural evolutions of colloidal gels under flow [25,27,45].…”
Section:  mentioning
confidence: 99%
“…double-layer polarization); in such cases, only moderate levels of attraction may be introduced, e.g. via polymer depletion effects [8][9][10][11][12]. Confocal microscopy was instrumental to these advances, yet may only be applied to transparent, index matched, systems, in which van der Waals forces are essentially absent.…”
mentioning
confidence: 99%
“…It can be expected that these denser network building blocks increase the percolation threshold when compared at overall volume fraction. On the other hand, recent work on colloidal gels 48 has demonstrated that gel elasticity is controlled by the volume fraction of locally isostatic clusters, which can be expected to increase more strongly with volume fraction in the denser systems. Here, the change in percolation threshold and volume fraction dependency of gel elasticity are shown to be linked.…”
Section: Making Stronger Gelsmentioning
confidence: 99%
“…The number of particle-particle contacts between clusters and the interaction between two particles at contact are found to be the source leading to the gel's elasticity. [46][47][48] The flow history also plays an important role. Koumakis et al showed that fully breaking the structure leads to more homogeneous and stronger gels, whereas preshear at low rates creates largely heterogeneous weaker gels with reduced elasticity.…”
Section: Introductionmentioning
confidence: 99%